2019
DOI: 10.1177/0969733019833130
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning for older people: The influence of ethnicity, religiosity, spirituality and health literacy

Abstract: In this discussion paper we consider the influence of ethnicity, religiosity, spirituality and health literacy on Advance Care Planning for older people. Older people from cultural and ethnic minorities have low access to palliative or end-of-life care and there is poor uptake of advance care planning by this group across a number of countries where advance care planning is promoted. For many, religiosity, spirituality and health literacy are significant factors that influence how they make end-of-life decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 71 publications
4
44
0
1
Order By: Relevance
“…Across a number of countries where is ACP is promoted, ethnic minority people's ACP readiness is generally low [46]: approximately 8-10% in Europe [4], 10-15% in Australia [47], and 10% or below in Asian countries. With a growing interest in the profound cultural influence on EOL decision-making [48], older, frail, and ethnic minority groups' ACP readiness is low, due to low access to palliative care.…”
Section: Influence Of a Collectivistic Culture And Family Decision-making On Acp Readinessmentioning
confidence: 99%
“…Across a number of countries where is ACP is promoted, ethnic minority people's ACP readiness is generally low [46]: approximately 8-10% in Europe [4], 10-15% in Australia [47], and 10% or below in Asian countries. With a growing interest in the profound cultural influence on EOL decision-making [48], older, frail, and ethnic minority groups' ACP readiness is low, due to low access to palliative care.…”
Section: Influence Of a Collectivistic Culture And Family Decision-making On Acp Readinessmentioning
confidence: 99%
“…37 Besides the religion, cultural and spiritual influence, HL is also critical to EOL decision-making. 38 LHL may hinder one's abilities to comprehend EOL terms and care options, to actively engage in patient-provider communities, and/or to express one's decisions so that the care received is concordant with his/her preferences. 39 Indeed, evidence has demonstrated that HHL has positive impact on hospice knowledge, attitude and decisionmaking.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, it is important to note that our study participants comprised only Japanese people. It has been shown that cultural, ethnic, and religious differences may influence one's sense of comfort when talking about death, treatment preferences, and knowledge about end‐of‐life care (Ohr et al, 2017; de Vries et al, 2019). Particularly, Asian older people often feel uncomfortable when talking about death, and older Japanese people tend to focus on maintaining their current lifestyles (Hirakawa et al, 2017; Ohr et al, 2017).…”
Section: Discussionmentioning
confidence: 99%